POWER FACTOR MONITORING AND CONTROLLING USING IoT - Manik; Naresh; Pruthviraj; Veeresh; T. Vinay Kumar (International Educational Journal of Science and Engineering, 2026)
This project focuses on improving the efficiency of AC electrical systems by monitoring and controlling the power factor using IoT technology with an ESP32 module. Power factor is the ratio of useful or true power (in kW) to apparent power (in kVA) consumed by electrical loads; especially inductive loads were current lags voltage. A low power factor indicates poor efficiency, causing higher power consumption, increased energy loss, and higher electricity costs. The system employs current and voltage sensors to accurately sense the electrical parameters and calculates power factor in real time. The ESP32 module displays these values on an LCD and sends the data to a cloud server for remote monitoring. When the power factor drops below a desired threshold, the system automatically triggers relay-based switching units to connect shunt capacitors, which provide leading reactive power to counteract the lagging reactive power of inductive loads. This correction reduces I²R losses in transformers and distribution equipment, frees up extra kVA capacity from the existing supply, reduces greenhouse gas emissions due to efficient power use, and lowers electricity bills. The ESP32 microcontroller, with its dual-core architecture and built-in Wi-Fi and Bluetooth, handles real-time processing, communication, and control functions effectively. The project also includes a regulated 5V DC power supply for stable operation of sensors and control circuits. This IoT-based automatic power factor correction system enables efficient and cost-effective energy management for industrial and commercial AC loads without manual intervention. It enhances system efficiency by increasing power factor toward unity through dynamic capacitor switching, ultimately improving energy savings and reducing environmental impact.